PENGARUH BOOK TAX DIFFERENCES TERHADAP KUALITAS LABA (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Rini Wati Pakpahan; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2017)
The purpose of this research is to examine empirically the influance of book tax differences to earning quality.  Book tax differences as independent variables divided to three group: Large Negative Book Tax Differences, Large Positive Book Tax Differences, and Small Book Tax Differences.  This research employ the dicretionary loan loss provisions and earning persistence as a proxies for earning quality. Population in this research are banking industry in Indonesia Stock Exchange in the period of 2010-2015. The sampel are 25 companies used purposive sampling method to select the sample. Regresion multiple with program SPSS 22 are used for testing hypotheses.The result indicted that book tax differences in banking industry have no effect to earning quality and there is no difference for earning persistensi and dicretionary loan loss provision base on magnitude of book tax differences.